2020
DOI: 10.3390/nu12041021
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metabolism and Vitamin D Implication in Gastroenteropancreatic Neuroendocrine Tumors

Abstract: Patients affected by gastroenteropancreatic–neuroendocrine tumors (GEP–NETs) have an increased risk of developing osteopenia and osteoporosis, as several factors impact on bone metabolism in these patients. In fact, besides the direct effect of bone metastasis, bone health can be affected by hormone hypersecretion (including serotonin, cortisol, and parathyroid hormone-related protein), specific microRNAs, nutritional status (which in turn could be affected by medical and surgical treatments), and vitamin D de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 128 publications
(210 reference statements)
2
13
0
1
Order By: Relevance
“…Except for a slight alteration of PTH in metachronous subjects, all these parameters have been found to be in the laboratory reference range, supporting the hypothesis that the presence of these metastases does not cause significant alterations in phospho-calcium homeostasis. This hypothesis is in agreement with other studies ( 17 , 18 ). A clarification should be made regarding vitamin D. In the literature, some studies report how patients with bone metastases from NET often present hypovitaminosis D, attributing this deficit to nutritional causes or to the clinical syndromes that are NET related ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Except for a slight alteration of PTH in metachronous subjects, all these parameters have been found to be in the laboratory reference range, supporting the hypothesis that the presence of these metastases does not cause significant alterations in phospho-calcium homeostasis. This hypothesis is in agreement with other studies ( 17 , 18 ). A clarification should be made regarding vitamin D. In the literature, some studies report how patients with bone metastases from NET often present hypovitaminosis D, attributing this deficit to nutritional causes or to the clinical syndromes that are NET related ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 94%
“…This hypothesis is in agreement with other studies ( 17 , 18 ). A clarification should be made regarding vitamin D. In the literature, some studies report how patients with bone metastases from NET often present hypovitaminosis D, attributing this deficit to nutritional causes or to the clinical syndromes that are NET related ( 18 , 19 ). In our research, we do not find this deficiency, but it should be emphasized that the majority of patients are put on early treatment with exogenous cholecalciferol.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, non-metastatic skeleton damage may include the traditional diagnosis of osteoporosis/osteopenia according to central dual-energy X-ray absorptiometry (DXA) and potentially complicated with (low-trauma or even spontaneous) osteoporotic fractures, in tumors such as lung and GEP-NEN, due to multiple hormonal, mechanical, nutritional, and metabolic factors (33). We propose the term carcinoid-related osteoporosis, even though the actual traditional terminology of 'carcinoid' tumor has been replaced by NEN/NET; yet, we consider that this expression clarifies a new clinical entity, different from neuroendocrine mechanisms underlying bone status under normal and abnormal conditions (34,35).…”
Section: Carcinoid-related Osteoporosismentioning
confidence: 99%
“…Recently, Altieri et al ( 8 ) reported that MEN1 patients with GEP-NETs had an increased prevalence of osteopenia and osteoporosis, mainly due to an altered nutritional status caused by excessive production of gastrointestinal hormones, medical therapy with somatostatin analogs and/or chemotherapies, and nutrient malabsorption subsequent to extensive surgical resection of duodenum and pancreas.…”
Section: Introductionmentioning
confidence: 99%